Modulation of Endoplasmic Reticulum Stress Influences Ischemia-Reperfusion Injury After Hemorrhagic Shock. Issue 5 (November 2019) - Obert, David Peter; Wolpert, Alexander Karl; Korff, Sebastian
ABSTRACT: Background: Impaired function of the endoplasmic reticulum (ER) results in ER stress, an accumulation of proteins in the ER lumen. ER stress is a major contributor to inflammatory diseases and is part of the pathomechanism of ischemia-reperfusion injury (IRI). Since severe traumatic injury is often accompanied by remote organ damage and immune cell dysfunction, we investigated the influence of ER stress modulation on the systemic inflammatory response and liver damage after hemorrhagic shock and reperfusion (HS/R). Material and Methods: Male C56BL/6-mice were subjected to hemorrhagic shock with a mean arterial pressure of 30 ± 5 mm Hg. After 90 min mice were resuscitated with Ringer solution. Either the ER stress inductor tunicamycin (TM), its drug vehicle (DV), or the ER stress inhibitor tauroursodeoxycholic acid (TUDCA) were added to reperfusion solution. Animals were sacrificed 14 h after shock induction and plasma concentrations of liver transaminases as well as inflammatory cytokines were measured. In addition, liver tissue sections were embedded in paraffin. For the quantification of hepatocellular damage hematoxylin and eosin stained tissue sections were analyzed. Furthermore, the topographic patterns of ER stress marker proteins were evaluated using immunohistochemistry. Results: ER stress modulation influenced the topographic pattern of ER stress marker proteins. The alterations were particularly seen in the transition zone between vital liver parenchyma and cell death areas. Furthermore, the application of tunicamycin during reperfusion inhibited the secretion of pro-inflammatory cytokines and increased the hepatocellular damage significantly. However, the injection of TUDCA resulted in a significantly reduced liver damage, as seen by lower transaminases and smaller cell death areas. Conclusion: ER stress modulation influences post-hemorrhagic IRI. Moreover, the ER stress inhibitor TUDCA diminished the hepatocellular damage following HS/R significantly. This may help to provide a therapeutic target to ameliorate the clinical outcome after trauma-hemorrhage.